ChemInform Abstract: Metal Catalyst‐Free Amination of 2‐Chloro‐5‐nitrobenzoic Acid in Superheated Water. Issue 17 (4th April 2013) - Lan, Cong; Xia, Zhi‐Ning; Li, Zheng‐Hua; Liang, Rong‐Hui
Abstract The environmentally‐friendly method can be successfully extended to reactions of 2‐chloro‐5‐nitrobenzoic acid with phenol and thiophenol.